Reflecting for Change: How Pedagogical Diploma Assignments Become Reflective Boundary Objects for Change of Practice - Hachmann, Roland; Carlsen, Dorthe; Albrechtsen, Thomas; Gammelgaard, Ole; Jensen, Anne (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
This study explores how pedagogical diploma assignments act as reflective boundary objects that support teachers in transforming their practice. Drawing on 212 assignments written by in-service teachers participating in a workplace-embedded diploma program in a Danish municipality, the study investigates how teachers reflect on and initiate pedagogical change by asking the following research questions: 1: Which pedagogical practices do the teachers notice and choose to investigate – and how? 2: What improvements to their own practice do they bring forward as a result of their investigations? Anchored in Dewey’s pragmatism, Benner’s praxeological approach, and Mason’s theory of noticing, the analysis reveals that teachers frequently focused on differentiated instruction, student motivation, inclusive practices, and classroom dynamics. These investigations lead teachers to critically examine their teaching through self-initiated inquiry. The assignments not only document changes in teaching methods but also demonstrate a shift in teachers’ professional self-understanding and conceptual framing of pedagogy. Teachers often narrate their learning processes, linking personal experiences to broader educational theories, thereby bridging formal coursework with the realities of everyday classroom practice. The findings highlight the transformative potential of diploma assignments when integrated within institutional models like the University School, which supports situated, autonomous inquiry. These reflective artifacts serve as tools for noticing, principled experimentation, and ethical reflection, enabling teachers to engage deeply with their practice. The study contributes to the field of reflective teacher education by presenting a model of partnership-based profession-didactical learning that emphasizes teacher agency and boundary-crossing reflection. It suggests that structured, experience-based inquiry can lead to meaningful, context-sensitive pedagogical development when embedded in supportive professional environments.